Designing integrative governance arrangements for policy performance in the Energy Union: evidence from seven member states. Issue 1 (2nd January 2023) - Bazzan, Giulia; Righettini, Maria Stella
ABSTRACT: With the adoption of the Energy Union Governance Regulation Framework, the European Commission called for better-integrated approaches to govern energy transition and climate policies across member states (MSs). Whether these aspirations for strengthened policy integration resulted into better-integrated domestic policies remains to be established. This article addresses two intertwined questions: first, whether and to what extent the MSs adopted better-integrated energy and climate policy, through adequate governance arrangements in their national energy and climate plans (NECPs). Second, whether a sound policy governance integration approach is related with better domestic energy and climate policy performances. We address these questions by applying the policy integration framework, comprising four integration dimensions: policy frame, subsystem involvement, policy goals, and policy instruments. To assess policy integration, we conduct a comparative qualitative content analysis of the NECPs of seven MSs (Italy, Finland, France, Romania, Hungary, Portugal, and Germany). We find that significant differences exist between the NECPs under scrutiny and that higher degrees of integration are related with higher degrees of energy and climate policy performance. Contrariwise, lower degrees of integration are related with lower degrees of energy and climate policy performance. We conclude with some advice for policymakers and reflect on implications for follow-up research.